2020
DOI: 10.4088/jcp.20m13395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of SPN-812 (Viloxazine Extended-Release) on QTc Interval in Healthy Adults

Abstract: Objective: To assess the effects of a supratherapeutic dose of SPN-812, a drug currently under investigation as a treatment for attention-deficit/hyperactivity disorder, on cardiac repolarization (QTc) in healthy adults. Methods: The study was conducted from June 27, 2018, to July 10, 2018. It had a double-blind, randomized, crossover design in which subjects received a 3-treatment sequence-placebo, 400 mg moxifloxacin, and 1,800 mg SPN-812 for 2 consecutive days (separated by at least a 3-day washout). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…There were no substantial differences between numbers of participants reporting AEs after treatment with viloxazine ER versus methylphenidate alone, nor when comparing viloxazine ER versus the combination. Although methylphenidate carries warnings of serious cardiovascular events [ 30 ], multiple clinical trials [ 25 – 29 ] and a recent study on cardiac repolarization [ 31 ] suggest viloxazine ER is not associated with increased cardiovascular risk, even at supratherapeutic doses. In the present study, the combination did not appear to increase these risks, as measured by blood pressure, pulse rate, or ECG parameters.…”
Section: Discussionmentioning
confidence: 99%
“…There were no substantial differences between numbers of participants reporting AEs after treatment with viloxazine ER versus methylphenidate alone, nor when comparing viloxazine ER versus the combination. Although methylphenidate carries warnings of serious cardiovascular events [ 30 ], multiple clinical trials [ 25 – 29 ] and a recent study on cardiac repolarization [ 31 ] suggest viloxazine ER is not associated with increased cardiovascular risk, even at supratherapeutic doses. In the present study, the combination did not appear to increase these risks, as measured by blood pressure, pulse rate, or ECG parameters.…”
Section: Discussionmentioning
confidence: 99%
“…dose of SPN-812 had no significant effect on cardiac repolarization or other ECG parameters, suggesting that it does not pose a risk of cardiac arrhythmias in healthy adults. 66 Cardiac AEs in SPN-812 Phase 3 study populations were infrequent, with only two incidences of tachycardia and one incidence of ECG T-wave inversion leading to discontinuation and considered related or possibly related to treatment across all four studies. [62][63][64][65] During intensive monitoring of suicidality, suicidal ideation and suicidal behavior were infrequent occurrences, with no incidence of suicidal ideation considered related to treatment and only one incidence of suicidal attempt in an SPN-812 treatment group considered possibly related to treatment.…”
Section: Viloxazinementioning
confidence: 95%
“…The study demonstrated that supratherapeutic (1800 mg q.d.) dose of SPN-812 had no significant effect on cardiac repolarization or other ECG parameters, suggesting that it does not pose a risk of cardiac arrhythmias in healthy adults 66 . Cardiac AEs in SPN-812 Phase 3 study populations were infrequent, with only two incidences of tachycardia and one incidence of ECG T-wave inversion leading to discontinuation and considered related or possibly related to treatment across all four studies 62-65 .…”
Section: Multimodal Agentsmentioning
confidence: 95%
“…In historic studies, viloxazine also did not increase the risk of adrenaline-induced cardiac arrhythmias [ 2 , 52 ]. In a contemporary study using supratherapeutic doses of viloxazine ER (1800 mg) in healthy adults, there was no effect on cardiac repolarization or other electrocardiogram parameters [ 54 ]. Minimal anticholinergic effects were found in human double-blind randomized studies of viloxazine 100 mg vs imipramine 50 mg [ 55 , 56 ], though both drugs induced transient tachycardia 4 h post-dose [ 55 ].…”
Section: Efficacy and Safety Of Viloxazine In Cns Conditions: Depression Anxiety Alcoholism And Epilepsymentioning
confidence: 99%